2020
DOI: 10.1186/s40463-019-0397-9
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative prediction of non-invasive follicular thyroid neoplasm with papillary-like nuclear features: A Canadian single-Centre experience

Abstract: BackgroundAn international group of experts recommended reclassifying non-invasive follicular variant of papillary thyroid cancers (FVPTC) as ‘non-invasive follicular thyroid neoplasm with papillary-like nuclear features’ (NIFTP) in April 2016. The purpose of this study was to establish preoperative clinical, laboratory, ultrasonographic, and cytological variables, which can differentiate NIFTP from FVPTC.MethodsWe conducted a retrospective chart review of consecutive patients from a single institution evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…Another study showed that on an initial and 1 week follow-up surveys, patients’ sense of taste was reduced at the initial one, but this had fallen to 75% when they filled the second survey one week after. 60% of the whole group reported that they could still differentiate between sweet, salty, sour, and bitter tastes at the time of the first survey, improving to 88.9% in the second survey [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that on an initial and 1 week follow-up surveys, patients’ sense of taste was reduced at the initial one, but this had fallen to 75% when they filled the second survey one week after. 60% of the whole group reported that they could still differentiate between sweet, salty, sour, and bitter tastes at the time of the first survey, improving to 88.9% in the second survey [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 More recent guidelines have allowed elective surgery to be performed with extra precaution to maintain protection at a high level for both patients and medical staff involved in the surgery. 2 Therefore, a tonsil surgery is possible during the COVID-19 pandemic with sufficient preparation and safety measures.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers are at the front line of the response to the pandemic and as such are exposed to several hazards that put them at risk of infection. Physicians and surgeons must assume responsibility to ensure that all necessary preventive and protective measures are taken to minimise occupational safety and health risks [ 19 , 20 ]. There is increasing concern among sinus and skull base surgeons in the neurosurgery and otolaryngology community due to exposure to a high viral load reservoir during endoscopic procedures in the nasal cavity and the nasopharynx [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also a risk of virus spread in smaller aerosols generated during various medical procedures that can cause airborne transmission over extensive distances [ 2 – 5 ]. Aerosol-generating medical procedures have been recognised as an important source for nosocomial transmission of emerging viruses [ 6 8 ]. It has been observed that once aerosolized, SARS-CoV-2 particles may remain viable and infectious in the air for at least 3 h [ 4 ].…”
Section: Introductionmentioning
confidence: 99%